(untitled) (Guanambi College Law Journal, 2020)
This research work analyzes the methodological assumptions of the interpretation and concretization of the right to privacy based on the decisions made by the Superior Court of Justice from 2012 to 2019. The objective is to check how such courts effect the balance of constitutional principles in collision. In addition, it is investigated whether the reasons for the decisions are adequate to the postulates of weighting and proportionality examination according to the theory of legal argument proposed by Robert Alexy.